The evaluation of the stress resistance of medical professionals present in the flooded area in the city of Krymsk and post-traumatic stress syndrome - A. V. Burlutskaya; Y. A. Prosolenko; E. A. Malysheva; A. V. Abushkevich; E. G. Potyagailo; V. G. Abushkevich (Кубанский научный медицинский вестник)
The observations were being carried out on 186 medical professionals who were sent to the flooded area-the city of Krymsk, and on 340 people who were already there. Their stress resistance was being evaluated by the psychological methods: the N.V. Kirsheva, N.V. Ryabchikova personality stress resistance self-test, the Cohen and Willianson stress resistance self test, the Holmes and Rage method of stress resistance and social adaptation evaluation, the method of neuropsychological resistance evaluation, the evaluation of disadaptation risk in stress «Prognosis» via the traumatic stress questionnaire. The comparison of the effectiveness of those psychological tests in the evaluation of the levels of stress resistance showed that the most informative method is «Prognosis». Among the evaluates persons, who were present in the flooded area there was determined 94 person with acute stress disorder. They were hospitalized. Three months after the disaster and rehabilitation 66 patients had symptoms of an acute stress disorder, and after 6 months 34 patients persisted.